The Effect of Firearms Regulatory Policies on Violent Crime Rates: Panel Data Regression Analysis - Marshinta, Fransisca Ully; Gunawan, M. Indra; Saraya, Sitta; Jixiong, Cai; Nirwana, Muhammad Alfaruq (Rechtsnormen: Journal of Law, 2024)
Background. Background The fields of public policy and criminological research continue to debate the influence of firearm regulatory policies on violent crime rates. Policies regarding the ownership and use of firearms vary between countries, with looser rules in certain countries. A fundamental question arises regarding how much these firearm regulatory policies have an impact on the level of criminal violence in society. Purpose. Using panel data, this research examines the impact of firearm regulatory policies on levels of criminal violence. Strict policies on firearms can reduce violence in society, that's the main goal of the research. This research also examines additional factors that may influence the relationship between firearms policy and violent crime. Method. This research method uses panel data analysis, this panel data includes information on firearms regulatory policies, violent crime rates, and other control variables from a number of countries or regions during the same time period. Regression analysis is used to evaluate how these variables relate to each other. Results. The results of the research from the results of the regression analysis show that a decrease in the level of violent crime in society is significantly related to the implementation of stricter firearm regulatory policies. Additionally, it has been proven that control variables such as education level, population density, and unemployment rate have a significant impact on violent crime rates. Conclusion. Thus, the results of this study show how important it is to implement strict firearms regulatory policies in efforts to combat violent crime. This research provides strong evidence that firearm regulatory policies can serve as an effective way to reduce levels of violence in society, although it is still necessary to consider other variables that may influence levels of violence.